2008
DOI: 10.1183/09031936.00061808
|View full text |Cite
|
Sign up to set email alerts
|

GenoType MTBDR assays for the diagnosis of multidrug-resistant tuberculosis: a meta-analysis

Abstract: The global extensively drug-resistant tuberculosis (TB) response plan calls for implementation of rapid tests to screen patients at risk of drug-resistant TB. Currently, two line probe assays exist, the INNO-LiPA1Rif.TB assay (Innogenetics, Ghent, Belgium) and the GenoType1 MTBDR assay (Hain LifeScience GmbH, Nehren, Germany). While LiPA studies have been reviewed, the accuracy of GenoType assays has not been systematically reviewed.The present authors carried out a systematic review and used meta-analysis met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
194
9
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(228 citation statements)
references
References 35 publications
22
194
9
3
Order By: Relevance
“…Results from several studies conducted elsewhere in the world to evaluate the performance of GenoType ® MTBDRplus assay, have reported similar results to our findings. A meta-analysis to validate GenoType ® MTBDRplus assays for the diagnosis of MultidrugResistant Tuberculosis showed 98%, 89% of sensitivity and specificity respectively [8]. Others studies presented similar results with a slight high specificity (100%) for RIF resistance in South Africa.…”
Section: Performance Of Genotype ® Mtbdrplus: Sensitivity Specificitsupporting
confidence: 55%
See 1 more Smart Citation
“…Results from several studies conducted elsewhere in the world to evaluate the performance of GenoType ® MTBDRplus assay, have reported similar results to our findings. A meta-analysis to validate GenoType ® MTBDRplus assays for the diagnosis of MultidrugResistant Tuberculosis showed 98%, 89% of sensitivity and specificity respectively [8]. Others studies presented similar results with a slight high specificity (100%) for RIF resistance in South Africa.…”
Section: Performance Of Genotype ® Mtbdrplus: Sensitivity Specificitsupporting
confidence: 55%
“…The GenoType ® MTBDRplus assay has been used as a tool for early TB and MDR-TB diagnosis to support the Programmatic Management of Drug Resistant Tuberculosis in the country to institute early treatment. It has been shown that GenoType ® MTBDRplus assay is the ideal technique to diagnose TB and MDR-TB and it accelerates the laboratory results for MDR-TB treatment and control [7,8]. Although the GenoType ® MTBDRplus assay has been validated in different settings with high burden of tuberculosis like in Thailand, Asia and in Africa like in South Africa [7,9], there is a need to evaluate its performance to ensure the acceptable performance in other settings with low TB burden like Rwanda.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the WHO approved the Hain GenoTypeMTBDRplus test for the rapid identification of M. tuberculosis complex strains in clinical isolates and the diagnosis of isoniazid and rifampin resistance by the detection of mutations in the inhA promoter and katG gene and in the rpoB gene, respectively (43). A recent meta-analysis demonstrated that the application of this test can reduce diagnostic delay (21), with a high sensitivity and specificity for identifying rifampin resistance, which is an important marker of MDR-and XDR-TB. Similarly, the XpertMTB/RIF test enables the genetic detection of rifampin resistance, with the added advantage that the result can be obtained in approximately 2 h for most smear-positive sputum samples and a significant number of smear-negative sputum samples (4,35).…”
mentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42] Conceptually similar to the INNO-Lipa Rif.tb assay, the MTBDRplus assay has been reported to have a diagnostic sensitivity of approximately 94% for detecting M tuberculosis DNA in smear-positive respiratory specimens. 33 It is of interest that most clinical evaluations of this device have focused on its use for susceptibility testing, not detection of M tuberculosis, so the performance characteristics for the latter use are less well defined.…”
Section: Line Probe Assaysmentioning
confidence: 99%